Antagonistic interactions between an invasive alien and a native coccinellid species may promote coexistence. (12th May 2016) - Hentley, William T.; Vanbergen, Adam J.; Beckerman, Andrew P.; Brien, Melanie N.; Hails, Rosemary S.; Jones, T. Hefin; Johnson, Scott N.
Summary: Despite the capacity of invasive alien species to alter ecosystems, the mechanisms underlying their impact remain only partly understood. Invasive alien predators, for example, can significantly disrupt recipient communities by consuming prey species or acting as an intraguild predator (IGP). Behavioural interactions are key components of interspecific competition between predators, yet these are often overlooked invasion processes. Here, we show how behavioural, non‐lethal IGP interactions might facilitate the establishment success of an invading alien species. We experimentally assessed changes in feeding behaviour (prey preference and consumption rate) of native UK coccinellid species ( Adalia bipunctata and Coccinella septempunctata ), whose populations are, respectively, declining and stable, when exposed to the invasive intraguild predator, Harmonia axyridis . Using a population dynamics model parameterized with these experimental data, we predicted how intraguild predation, accommodating interspecific behavioural interactions, might impact the abundance of the native and invasive alien species over time. When competing for the same aphid resource, the feeding rate of A. bipunctata significantly increased compared to the feeding in isolation, while the feeding rate of H. axyridis significantly decreased. This suggests that despite significant declines in the UK, A. bipunctata is a superior competitor to the intraguild predator H. axyridis . In contrast, the behaviour of non‐declining C. septempunctata was unaltered by the presence of H. axyridis . Our experimental data show the differential behavioural plasticity of competing native and invasive alien predators, but do not explain A. bipunctata declines observed in the UK. Using behavioural plasticity as a parameter in a population dynamic model for A. bipunctata and H. axyridis, coexistence is predicted between the native and invasive alien following an initial period of decline in the native species. We demonstrate how empirical and theoretical techniques can be combined to understand better the processes and consequences of alien species invasions for native biodiversity. Abstract : The authors demonstrate how competition between native and invasive coccinellids induces plastic changes in the feeding rate of two species; a previously undocumented behavioural response in coccinellids. These results are incorporated into a well‐established population dynamic model, revealing how a seemingly innocuous change in feeding behaviour might influence the invasion process.